2009
DOI: 10.1021/ci900286s
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of Aqueous Solubility: The Solubility Challenge

Abstract: The dissolution of a chemical into water is a process fundamental to both chemistry and biology. The persistence of a chemical within the environment and the effects of a chemical within the body are dependent primarily upon aqueous solubility. With the well-documented limitations hindering the accurate experimental determination of aqueous solubility, the utilization of predictive methods have been widely investigated and employed. The setting of a solubility challenge by this journal proved an excellent oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 38 publications
1
90
0
Order By: Relevance
“…Dissolution from a dosage form depends both on the solubility of the drug by itself and the release pattern of the dosage form in which it is administered (1). A drug's solubility is determined by many factors, such as molecular weight, lipophilicity, crystal or amorphous state, and pKa (2)(3)(4). Studies showed that a poor drug solubility might lead to limited drug absorption, but formulation processes can overcome such issues if the dissolution mechanism is understood (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissolution from a dosage form depends both on the solubility of the drug by itself and the release pattern of the dosage form in which it is administered (1). A drug's solubility is determined by many factors, such as molecular weight, lipophilicity, crystal or amorphous state, and pKa (2)(3)(4). Studies showed that a poor drug solubility might lead to limited drug absorption, but formulation processes can overcome such issues if the dissolution mechanism is understood (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Early estimation of dissolution behavior and investigation of the influence of formulation factors on solubility is essential for pharmaceutical formulation development (1,2,13). Using In silico methods in the drug discovery stage to estimate drug dissolution can eliminate many trial and error experiments and save time and money (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both types of models have been used in drug-likeness analysis and as efficient filters for compound screening. To assess the quality of these models, Hewitt et al (2009) compared four approaches, including simple linear regression, artificial neural networks (ANNs), category formation, and available in silico models. No one approach could accurately predict the solubility, but the simple regression approach was superior to the more complex modelling methods due to its lower probability of over-fitting.…”
Section: Solubilitymentioning
confidence: 99%
“…2 For instance, a recent prediction of the intrinsic solubilities of 32 crystalline druglike molecules in water using a data set of accurately determined solubilities of 100 compounds was challenged 3 and resulted in about 100 contributions. 4 Only a few of the top 10 successful results have been published, 5,6 which present simple and straightforward models and reveal problems in modeling of solubility as well.…”
Section: Introductionmentioning
confidence: 99%